DETERMINATION OF SCABIES RISK FACTORS BASED ON PERSONAL HYGIENE, CONTACT HISTORY, AND ENVIRONMENTAL CONDITIONS: A LITERATURE REVIEW - Reka Maulidar; Roslita (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
Scabies is a contagious skin disease that continues to pose a public health problem, particularly in developing countries with inadequate environmental conditions and poor hygiene practices. The disease is caused by an infestation of the mite Sarcoptes scabiei var. hominis, and its transmission is strongly influenced by behavioral, physical environmental, and socioeconomic factors. This literature review aims to analyze the factors contributing to the incidence of scabies based on empirical evidence from recent studies. The literature search was conducted through several scientific databases using keywords related to scabies, risk factors, personal hygiene, contact history, humidity, and household crowding. The analyzed articles include primary research studies and scientific reviews published within the last 10 to 15 years that met the inclusion criteria. The findings indicate that poor personal hygiene is the most consistently reported risk factor. Infrequent bathing, irregular changing of clothes, and inadequate cleanliness of bedding significantly increase the likelihood of infection and reinfection. Contact history becomes the most dominant mechanism of transmission, both through direct skin-to-skin contact and through shared personal items. Environmental factors such as overcrowded living conditions and poor ventilation further elevate the risk by increasing the frequency of close contact and creating microclimatic conditions that support myth survival. Low levels of community knowledge about symptoms, transmission, and prevention also contribute to the persistently high incidence of scabies.